CXCL13 as a novel marker for diagnosis and disease monitoring in pediatric PTLD - Schiffer, L.; Henke-Gendo, C.; Wilsdorf, N.; Hussein, K.; Pape, L.; Schmitt, C.; Haller, H.; Schiffer, Mario; Klein, C.; Kreipe, H.; Maecker-Kolhoff, B. (American Journal of Transplantation, 2012)
Posttransplant lymphoproliferative disease (PTLD) is a severe complication of immunosuppressive treatment in organ-grafted children. Early diagnosis of PTLD is hampered by both unspecific clinical symptoms and lack of easy accessible markers. The homeostatic chemokine CXCL13, which plays a crucial role in B-cell homing and lymphoid organ development, is expressed in some lymphomatous diseases. This study aims to investigate whether serum CXCL13 (sCXCL13) levels correlate with occurrence and regression of PTLD in pediatric solid-organ graft recipients. Serum samples from PTLD patients (n = 21), patients with Epstein-Barr virus (EBV) reactivation (n = 18), and healthy age-matched controls (n = 19) were tested for CXCL13 using a commercially available ELISA kit. sCXCL13 levels were significantly higher in PTLD patients than in healthy children. PTLD patients had also higher sCXCL13 values than pediatric solid-organ recipients with EBV reactivation. An increase in sCXCL13 levels was observed from EBV reactivation to PTLD diagnosis in most cases. Elevated sCXCL13 levels were detected up to 2 years prior to PTLD diagnosis and correlated well with response to cytoreductive treatment in individual patients. sCXCL13, thus, may be a readily available surrogate marker for the diagnosis of PTLD and for monitoring of response to treatment in patients with initially elevated sCXCL13 levels. Serum levels of B cell-attracting chemokine CXCL13 are associated with occurrence and regression of posttransplant lymphoproliferative disorders in pediatric solid organ graft recipients. © Copyright 2012 The American Society of Transplantation and the American Society of Transplant Surgeons.
CRIS-Team Scopus Importer:2020-11-12
Keywords: CXCL13; pediatric; posttransplant lymphoproliferative disease; PTLD; solid-organ transplantation